Development of a Ceramic Foam Filter for Filtering Molten Aluminum Alloy in Casting Processes - Bagherian, Ehsaanreza (2009)
Metal casting component are found in 90 percent of manufactured goods and equipment, from critical components for aircraft and automotive industry to home applications. However, molten metal used to produce metal casting in practice generally contains impurities and inclusions which are deleterious to final cast metal product. Currently, filtration technique by using ceramic foam filter has been accepted as a successful method of reducing inclusions from molten metal during the casting of metal parts. The present research has been done to fabricate and improve a ceramic foam filter for using in filtration of molten metal, especially aluminium based alloys. It is an objective of the present innovation to provide a ceramic foam filter characterized by cost of raw materials. Ceramic foam filters are produced by impregnating polyurethane foam with ceramic slurry, drying, baking and finally firing the foam in the oven. Experimental tests were carried out to the filters to measure dimensions, weight, cold compression strength, and permeability properties before pouring process. After pouring process, the filter was cut into several sections to measure the macro and microstructure of the filter and ensure that impurity particles captured by a filter. Thermal shock properties, obtained from pouring liquid aluminium when filter was placed in the gating system to ensure that the filters could withstand temperatures of aluminium alloys. Further experiments were carried out to investigate and determine the efficiency of produced ceramic foam filter on quality of cast products. The result obtained in this investigation, the mechanical properties for aluminum LM6 alloy sand casting increased when ceramic foam filter was inserted into the gating system. A produced filter by using new materials is economical to be produced. Further more, the analysis data shows present innovation filter which can be made in any shape and size, has excellent thermal shock resistance, adequate compressive strength, acceptable density and permeability properties.